Unraveling the Amino Acid Synthesis in Maturity Sesame Seeds Based on the Integrative Analysis of Transcriptome and Metabolome - Yinping Zhang; Yuanyuan Zhang; Xiangyu Zhou; Nan Yang; Duoqi Zhou; Kiran Thakur; Qiang Wang; Carlos L. Cespedes‐Acuña; Haiyang Zhang; Hongmei Miao; Zhaojun Wei (Food Frontiers)
ABSTRACT Sesame plays a vital role in food industry due to its high oil yield, antioxidant potential, and substantial protein content. Notably, there are significant differences in amino acid composition in sesame seeds at various developmental stages. However, the molecular basis and regulatory mechanism underlying amino acid production largely remain unexplored. To unravel these mechanisms, we analyzed the metabolome and transcriptome profiles of a sesame variety across four distinct growth stages (S1–S4). Our analysis identified a total of 17 amino acids, with glutamic acid (Glu), arginine (Arg), proline (Pro), and tyrosine (Tyr) exhibiting significantly higher abundances in mature stages. This increased abundance correlated with the elevated expression of genes involved in amino acid synthesis and regulatory genes. Using weighted gene co‐expression network analysis, we discovered modules associated with glutathione metabolism, arginine biosynthesis, proline, and tyrosine synthesis, along with candidate genes that regulate amino acid production and metabolism. Notably, the differential expression of genes within the amino acid pathways resulted in significant variations in the contents of Glu, Arg, Pro, and Tyr at the mature stage (28 days after flowering, S4) compared to other growth stages. Correlation analysis revealed strong association among the enzymes glutamine synthetase (GS), glutamate/aspartate–prephenate aminotransferase (PAT), and polyamine oxidase (PAO) with the 17 amino acids, suggesting their potential role in the amino acid synthesis. Our findings provide novel insights into the synthesis and accumulation of amino acids during the growth stages of sesame seeds, highlighting key regulatory genes and metabolic pathways involved in this process. Our study lays the groundwork for future studies aiming to enhance the nutritional quality and yield of sesame varieties.